LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN KEPERCAYAAN DIRI PESERTA DIDIK - Muslima Muslima (Pusat Studi Wanita UIN Ar-Raniry, 2018)
This study aims to determine the effect of group guidance services on increasing the confidence of students in the Model Gandapura MTsN, by helping students to improve self-motivation, self-control independently and independently. Can develop self-confidence in the strengths and advantages of oneself, and to find out information objectively about the general description of students' confidence in interacting in the classroom before being given group guidance services. The research method used pre-experimental designs with the type of one-group pretest-posttest design by involving one group that was given a pretest, then given treatment and given a post-test. The success of the treatment will be obtained by comparing the pretest and posttest values. The research subjects were 21 people who were chosen proportionally from 280 students. The results showed that students with low self-confidence: easily anxious in facing problems with a certain level of difficulty, sometimes nervous when talking, often being alone from groups that were considered more than themselves. However, the problem can be handled properly by providing group guidance services. Students who take part in group guidance activities can directly practice creating group dynamics. By practicing speaking, responding, listening and feeling in a group atmosphere. Group guidance services are a place of self-development in order to learn to interact positively and effectively in small groups. In this study the influence of group guidance on students' self-confidence can be seen with the criteria that students feel strong towards the actions taken, students feel accepted by the group and students have a sense of their daily attitudes.